THE IMPACTS OF AFTA-COMMON EFFECTIVE PREFERENTIAL TARIFFS ON THE TRADE DIVERSION AND TRADE CREATION OF SYNTHETIC RUBBER AND FACTICE FROM OIL IN INDONESIA - Amir, Faizal; Zuhroh, Idah (Muhammadiyah International Journal of Economics and Business, 2018)
Rubber and its products are one of the exported commodities listed in Indonesia’s ten primary exported commodities (Ministry of Trade 2015). Different from other rubber products, the impor of synthetic rubber and factice from oil have increased significantly since the establishment of the AFTA-CEPT with approximately 7 thousand registered products in the Inclusion List (IL) in 2002. This study aimed to analyze the competitiveness of synthetic rubber and factice krom oil among the members of AFTA countries and analyze the impacts of trade creation and Trade diversion on the implementation of the CEPT-AFTA on synthetic rubber and factice oil krom Indonesia, particularly in the 11 countries of origin of imports during the period from 2001 to 2013 by using a gravity model, which was analyzed using static data panel. Based on the results of RCA (Revealed Comparative Advantage), the competitiveness of synthetic rubber and factice oil from Indonesia is very low among four ASEAN countries, while Thailand is the top exporting countries in ASEAN region. The results of the panel data analysis showing variables which have positive influence are Indonesia’s real GDP and real GDP of the country of origin of imports, while variables with negative effect are economic distance and Indonesia’s real exchange rate compared to the country of origin of imports. The implementation of AFTA-CEPT brought against Trade diversion and creation of synthetic rubber and factice oil from Indonesia will have impacts on the existence of trade creation because part of the domestic production of synthetic rubber Ana factice oil from Indonesia will be replaced with imports from member countries and there is on trade diversion.